1989
DOI: 10.1007/bf00006064
|View full text |Cite
|
Sign up to set email alerts
|

Significance of a low oxygen layer for a Daphnia population in Lake Yunoko, Japan

Abstract: Population dynamics and vertical migration of Daphnia longispina in Lake Yunoko were studied. The Daphnia population was small in spring and early summer, probably because of high predation pressure by fish. The population grew in midsummer, when thermal stratification developed and the dissolved oxygen became very low in the deeper layer of the hypolimnion. In this season, adults of D. Zongispina concentrated in the daytime near the lake bottom, where fish were absent because of the anoxic conditions, but asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
36
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 22 publications
(23 reference statements)
2
36
0
1
Order By: Relevance
“…In these lakes, warm-water fish species dominate and are constrained to feeding in the surface waters. The hypoxic deeper waters may actually act as an important refuge for zooplankton from fish predation (Hanazato et al 1989;Wright and Shapiro 1990;Tessier and Welser 1991) as well as visually feeding invertebrate predators, such as Bythotrephes (Manca et al 2007;Manca and DeMott 2009). In oceans, the more transparent systems are generally associated with warmer, open-ocean, low-latitude habitats, such as subtropical gyres, and therefore, in contrast to freshwater systems, are usually populated by warm-water fish species.…”
mentioning
confidence: 99%
“…In these lakes, warm-water fish species dominate and are constrained to feeding in the surface waters. The hypoxic deeper waters may actually act as an important refuge for zooplankton from fish predation (Hanazato et al 1989;Wright and Shapiro 1990;Tessier and Welser 1991) as well as visually feeding invertebrate predators, such as Bythotrephes (Manca et al 2007;Manca and DeMott 2009). In oceans, the more transparent systems are generally associated with warmer, open-ocean, low-latitude habitats, such as subtropical gyres, and therefore, in contrast to freshwater systems, are usually populated by warm-water fish species.…”
mentioning
confidence: 99%
“…In a study as in [11], in Lake Yunoko it was found that the population of pond smelt are almost absent in anoxic areas where the dissolved oxygen was below 3 mg/l, showing that dissolved oxygen concentration of lake water has a strong influence on the population dynamics of the pond smelt (Hypomesus olidus). Hasenbein [14] showed that negative correlation exists between turbidity of water and feeding frequency of juvenile delta smelt (Hypomesus transpacificus) from the San Francisco Bay Delta, USA.…”
mentioning
confidence: 98%
“…Pond smelts have been shown to be affected by biological and environmental factors previously [11]- [14]. In a study as in [11], in Lake Yunoko it was found that the population of pond smelt are almost absent in anoxic areas where the dissolved oxygen was below 3 mg/l, showing that dissolved oxygen concentration of lake water has a strong influence on the population dynamics of the pond smelt (Hypomesus olidus).…”
mentioning
confidence: 99%
“…This poses a problem for zooplankters performing vertical migration as the lack of oxygen experienced by the animals during the daytime results in a reduced growth rate (Hanazato and Dodson, 1995) and a lower reproductive output (Hanazato et al, 1989). However, zooplankters are still found in low-oxygen layers (Hanazato et al, 1989;Hanazato, 1992;Duncan et al, 1993).…”
mentioning
confidence: 99%
“…This poses a problem for zooplankters performing vertical migration as the lack of oxygen experienced by the animals during the daytime results in a reduced growth rate (Hanazato and Dodson, 1995) and a lower reproductive output (Hanazato et al, 1989). However, zooplankters are still found in low-oxygen layers (Hanazato et al, 1989;Hanazato, 1992;Duncan et al, 1993). A possible explanation for this phenomenon might be that these oxygen-depleted hypolimnetic layers provide not only a light refuge, because the most important planktivorous fish are visual predators, but also an oxygen refuge, as most fish are obligate aerobes and therefore unable to penetrate low-oxygen layers for longer periods (Hanazato et al, 1989;Wright and Shapiro, 1990).…”
mentioning
confidence: 99%